To the problem of medical and psychological support system «mother – child» under different feeding conditions - Маркова, Маріанна Владиславівна; Кришталь, Євген Валентинович; Лобойко, Л. І. (Psychological Counseling and Psychotherapy)
Based on a comprehensive examination within one year after successful uncomplicated births 154 women and their children, it is proved that the type of feeding is not the key factor in the formation of relationships in the «mother – child» as opposed to psychological well-being and readiness for motherhood, parenting awareness, family relationships. Identified psycho-emotional, individual psychological and psychosocial factors interact strain «mother – child». Evidence-based, designed and implemented a system of medical and psychological support aimed at optimizing the interaction in the mother-child dyad, which consists of five stages and aims at: a) reduction of postpartum psychopathological symptoms, normalization of maternal psycho-emotional sphere, b) search for and activation of individual, dyadic and family resources, and c) the development of individual and marital adaptation strategies for solving problems, and d) improve maternal, dyadic and family psychological competence. The general principle of the developed system is its integrative and basic facilities - group, cognitive-behavioral, personal, family and cognitively oriented psychotherapy, support – estetotherapy (libraries, music-, art-therapy), and relaxation techniques. Implementation of this medical and psychological support possible to achieve reduction of psychopathological symptoms of women, raise awareness of parenting and improve the level of psychomotor development of children (p≤0,05).